NARINGENIN-LOADED CHITOSAN NANOPARTICLES FORMULATION, AND ITS IN VITRO EVALUATION AGAINST T47D BREAST CANCER CELL LINE - Winarti, Lina; Ruma Kumala Sari, Lusia Oktora; Nugroho, Agung Endro (Indonesian Journal of Pharmacy, 2015)
Naringenin (NAR), a natural flavonoid aglycone of naringin has been extensively investigated for its pharmacological activities, including anti-tumor effects. However, its poor bioavailability  has been identified as the single most important challenge in oral drug delivery. Based in this condition, it is used nanoencapsulation to increase the effectiveness of  NAR as anti-cancer. The objectives of this research are to develop the formulation of  NAR-loaded nanoparticles (NARNPs) as well as to evaluate its potential as anti-cancer against T47D breast cancer cells line. NARNPs is prepared through the method of ionic gelation, meanwhile its characteristic is evaluated through photon correlation spectroscopy (PCS), transmission electron microscopy (TEM), fourier transform infra-red spectroscopy (FTIR), and different scanning calorimeter (DSC). The result of MTT test and cellular uptake indicate that NARNPs increase citotoxicity and internalization of NAR to the cells compared to the free NAR. The result of qualitative apoptosis study using fluorescence microscope indicates that both free NAR and NARNPs are able to induce apoptosis. It can be conclude that Chitosan  nanoparticles–TPP  conjugates  have  the  capability  to encapsulate naringenin hence increase the cellular uptake and cytotoxcicity of naringenin against T47D cell line. NARNPs also can induce the apoptosis effect.Keywords: NAR, Chitosan (CS), ionic gelation, nanoparticles